Pengaruh Penerapan Metode Qira’aty Terhadap Kemampuan Membaca Al-Qur’an Siswa - Fauziah, Hapsah; Kurniati, Anggun (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
The study of the Qur'an is a fundamental and inseparable part of Islamic Religious Education (PAI). PAI is a core subject in every Islamic educational institution. However, a case study at an educational institution revealed that many students still struggle to achieve good scores in practical Qur'anic reading. Common issues include incorrect pronunciation of letters (makharijul huruf) and neglect of tajweed rules while reading the Qur'an. One contributing factor to these problems is the method used to teach Qur'anic reading in PAI classes. To address these challenges, the Qira’aty method was implemented as a technique to enhance students' Qur'anic reading abilities. This study aims to describe the following: the implementation of the Qira’aty method, the Qur'anic reading proficiency of students, and the impact of the Qira’aty method on improving students' Qur'anic reading skills. The research employs a descriptive quantitative approach, involving interviews and direct field observations to examine the current factual phenomena. The data collected were analyzed both qualitatively and statistically. The results show that the average score for the implementation of the Qira’aty method is 4.11, which falls into the "very good" category. Similarly, the average score for students' Qur'anic reading proficiency is 4.07, also categorized as "very good." Furthermore, the application of the Qira’aty method in class showed a significant impact on students' reading abilities, with an F value of 8.69, which is greater than the critical value of 4.24 (Fhitung > Ftabel). Thus, it can be concluded that the Qira’aty method significantly enhances students' proficiency in reading the Qur'an.  Keywords: Qira’aty Method, Qur'anic Reading Proficiency, Islamic Religious Education